Adaptive force/position NN control of asymmetric teleopertion system based on fuzzy CMAC - Hua Chen; Baoyu Shi (Discover Applied Sciences)
Abstract With the continuous advancement of industrial automation, the performance requirements for metallurgical industrial robots, especially in teleoperation systems, are increasingly demanding. This paper presents an adaptive force/position control algorithm based on Fuzzy CMAC (Cerebellar Model Articulation Controller) for an asymmetric teleoperation system. The system consists of a novel 6-degree-of-freedom master robot and a Baxter slave robot. Our design focuses on addressing tracking and transparency issues in asymmetric systems. Experimental results demonstrate that the proposed control algorithm significantly outperforms the adaptive fuzzy PID control algorithm in terms of control performance, meeting the requirements for stability, tracking, and transparency in asymmetric teleoperation systems. The innovation of this study lies in the development of a new 6-DOF haptic device and its successful application in an asymmetric teleoperation system, enhancing control precision and user experience. The results of this research not only hold application potential in the metallurgical field but also provide new technical pathways for the future development of teleoperation systems.